1997
DOI: 10.1046/j.1365-2036.1997.113284000.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of heartburn relapse by low‐dose famotidine: a test meal model for duration of symptom control

Abstract: Aim: To establish whether patients taking famotidine 10 mg to treat an episode of heartburn were protected from a recurrence of symptoms after a subsequent test meal. Methods: Frequent heartburn sufferers (n=366) were randomized to receive double blind treatment with famotidine 10 mg or 2×250 mg chewable alginate tablets within 30 min of a spontaneous episode of heartburn. After 4 h, patients with no or slight residual symptoms consumed a meal likely to induce heartburn. Over the next 4 h patients recorded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
1
12
2
Order By: Relevance
“…The finding that fewer customers using H 2 ‐receptor antagonists experienced return of symptoms than those who had previously used simple antacids is in agreement with the results of published work from controlled studies [1, 2]. The results also suggest that H 2 ‐receptor antagonists had a longer effect on symptom relief than alginate‐containing preparations [3].…”
Section: Discussionsupporting
confidence: 88%
“…The finding that fewer customers using H 2 ‐receptor antagonists experienced return of symptoms than those who had previously used simple antacids is in agreement with the results of published work from controlled studies [1, 2]. The results also suggest that H 2 ‐receptor antagonists had a longer effect on symptom relief than alginate‐containing preparations [3].…”
Section: Discussionsupporting
confidence: 88%
“…There is evidence that this lower dose raises gastric pH, and can be effective for some hours, although as previously mentioned the onset of action is delayed compared with simple antacids 44–48 . Effectiveness has also been demonstrated in patients with heartburn 49 . Thus, despite the intuitive feeling that the over‐the‐counter dosage is not enough, this view is not supported on present evidence, although perhaps it is effective only for mild disease.…”
Section: Drugs For Dyspepsia/heartburncontrasting
confidence: 53%
“…There is some evidence that OTC drugs are effective in preventing post-prandial dyspepsia and heartburn but there are few symptom-based studies in the literature. 14,15 In this study we have demonstrated that the gastric acid inhibitory effect of ranitidine is superior to cimetidine 200 mg in the 10 h after an oral dose. We have also shown that the effect of ranitidine 75 mg, taken around midday, can persist for 10±15 h. It is uncertain whether this late and modest effect can translate into a symptomatic bene®t for patients.…”
Section: Discussionmentioning
confidence: 85%